Targeting 7KCh-Induced Cell Death Response Mediated by p38, P2X7 and GSDME in Retinal Pigment Epithelium Cells with Sterculic Acid - Ana Pariente; Rafael Peláez; Rodrigo Ochoa; Álvaro Pérez-Sala; Ángela Villanueva-Martínez; Miriam Bobadilla; Ignacio M. Larráyoz (MDPI AG, 2023)
Age-related macular degeneration (AMD) is the main cause of blindness in developed countries. AMD is characterized by the formation of drusen, which are lipidic deposits, between retinal pigment epithelium (RPE) and the choroid. One of the main molecules accumulated in drusen is 7-Ketocholesterol (7KCh), an oxidized-cholesterol derivative. It is known that 7KCh induces inflammatory and cytotoxic responses in different cell types and the study of its mechanism of action is interesting in order to understand the development of AMD. Sterculic acid (SA) counteracts 7KCh response in RPE cells and could represent an alternative to improve currently used AMD treatments, which are not efficient enough. In the present study, we determine that 7KCh induces a complex cell death signaling characterized by the activation of necrosis and an alternative pyroptosis mediated by P2X7, p38 and GSDME, a new mechanism not yet related to the response to 7KCh until now. On the other hand, SA treatment can successfully attenuate the activation of both necrosis and pyroptosis, highlighting its therapeutic potential for the treatment of AMD.